Enhancing Pragmatic Competence in Language Lessons for School children - Zhanysbekova , Shaizat; Nurgali, Saule; Akbota, Shoibekova; Gulzira , Sagnaeva; Nursaule, Aitbayeva; Nurkassym , Asimbay (Journal of Ecohumanism, 2024)
The study focuses on enhancing the pragmatic competence of schoolchildren in language lessons. Pragmatic competence, the ability to use language effectively and appropriately in various social contexts, is crucial for communication and social interaction. This research investigates methods for improving this competence in the language classroom by implementing targeted pedagogical strategies. The study adopts an experimental approach, comparing the outcomes of pragmatic-focused lessons against traditional language teaching. Results demonstrate that explicit instruction on pragmatics significantly improves students' understanding of context, politeness strategies, and social appropriateness in language use. The study concludes by recommending strategies for integrating pragmatic competence into regular language curricula to foster more effective communicators.